The Relationship Between Plasma Eosinophil Count and Coronary Artery Ectasia - Demir, Mehmet (Cardiol Res, 2013)
BACKGROUND: The pathophysiology of coronary artery ectasia (CAE) has not been clearly identified, although multiple abnormalities including arteritis, endothelial dysfunction, and atherothrombosis have been reported. It is known that eosinophils play an important role in inflammation and thrombosis. Also vascular anomalies such as aneurysm have been noted in patients with hypereosinophilic syndromes. We aimed to compare the numbers of eosinophil counts of the patients CAE versus controls. METHODS: This study included 50 CAE patients (20 male, mean age 60.26 ± 10.6 years) and 30 control person (10 male, mean age 57.86 ± 11.6 years). These participants were performed concurrent routine biochemical tests and neutrophil, lymphocyte, eosinophil count and mean platelet volume (MPV) on whole blood count. These parameters were compared between groups. RESULTS: Baseline characteristics of the study groups were comparable. CAE patients had a higher MPV value, eosinophil, neutrophil lymphocyte ratio (NLR) than controls (8.5 ± 1 vs 76.2 ± 1.6 fl and 0.198 ± 0.14 vs 0.093 ± 0.058 and 3.0 ± 2.5vs 1.14 ± 0.9; P < 0.001, 0.002 and 0.028 respectively). CONCLUSION: As a result, our study revealed a relationship between eosinophil count, NLR and MPV in patients with CAE.